2015
DOI: 10.1049/iet-rsn.2014.0229
|View full text |Cite
|
Sign up to set email alerts
|

Joint inference of dominant scatterer locations and motion parameters of an extended target in high range‐resolution radar

Abstract: A target of interest measured by a high range resolution radar may be modelled by multiple dominant points of reflections referred to as dominant scatterers. In this paper a non-linear state space setting is used to model the states and measurements of a target moving in the down-and cross-range dimensions. A resample-move particle filter with simulated annealing is successfully used to jointly infer the locations of the dominant scatterers and the motion parameters of the target. A novel technique for the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several models and approaches have been proposed for [4–6], including the spatial probability distribution model [7], the random hypersurface model [8, 9], the random matrix approach [10–13], the multiple hypothesis tracking [14], and the probability hypothesis density filters [15–17]. In addition, some modern surveillance sensors are able to provide the target's down‐range and cross‐range extent measurements on a single extended object along the line of sight (LOS) [18]. Using range extent measurements benefits track retention and recognition of convoys [19, 20] in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several models and approaches have been proposed for [4–6], including the spatial probability distribution model [7], the random hypersurface model [8, 9], the random matrix approach [10–13], the multiple hypothesis tracking [14], and the probability hypothesis density filters [15–17]. In addition, some modern surveillance sensors are able to provide the target's down‐range and cross‐range extent measurements on a single extended object along the line of sight (LOS) [18]. Using range extent measurements benefits track retention and recognition of convoys [19, 20] in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the final part of the paper, it is shown that the derived results on quasi‐Born approximation are only a very specialised case of a more encompassing concept (referred to as ‘iso‐Qc data’) that has broad practical applicability such as in backscattering‐based imaging that arises, e.g. in monostatic radar, synthetic aperture radar (SAR), and inverse SAR systems [15–17, 25, 26].…”
Section: Introductionmentioning
confidence: 99%